The Influence of Transformational Leadership Style and Emotional Intelligence on the Performance of Generation Z Employees in the Hybrid Work Era (A Study at PT Sari Mas Permai, Palembang) - Vemi Fytaloka; Dini Pratiwi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to examine the influence of transformational leadership style and emotional intelligence on the performance of Generation Z employees in the context of hybrid work at PT Sari Mas Permai, Palembang. The post-pandemic work landscape has driven companies to adapt to flexible work systems, which require new managerial approaches in managing the younger generation of employees. This research employs a quantitative approach using a survey method involving 100 Generation Z employees working in the administration and marketing departments. The research instruments were tested for validity and reliability, then analyzed using multiple linear regression.The results show that transformational leadership style has a positive and significant effect on employee performance, with a coefficient of 0.328 and a significance value of 0.013. Meanwhile, emotional intelligence exerts a more dominant influence with a coefficient of 0.467 and a significance value of 0.000. Simultaneously, the two independent variables explain 62.4% of the variation in employee performance (R² = 0.624). These findings affirm that the combination of inspirational leadership and strong emotional abilities are key factors in enhancing the performance of Generation Z in a dynamic and digital work environment.The implications of this study highlight the importance of developing a transformative leadership model and strengthening emotional intelligence as part of human resource management strategies. Companies need to provide training and mentoring programs to foster a work culture that supports adaptation and productivity among young employees in the hybrid work era.